Partidos políticos e processo decisório em Araraquara-SP (1997-2008) - Silva, Bruno Souza da [UNESP] (2013)
This research aims to analyze how councilors acting and behaving in municipal decisionmaking process, so that was chosen as a case study the decision-making process regarding relations Executive-Legislative branches in the city of Araraquara in the period between 1997 and 2008, with municipality located in the central region of the state of São Paulo, about 270 Km away from capital. Theoretical and methodological notes follow the literature on the Brazilian-legislature, which indicates absence of research on institutional aspects and behavior of the parties in political decisions in the sublevels of government, especially at the local levels. Thus, the research method used was concentrated in working endogenous variables to the legislature, as the variables: (i) legislative process, (ii) political parties, (iii) parliamentary rights, and (iv) parliamentary devices in addressing the role of councilors and parties on the basis of government and opposition over the three legislatures that composes the analyzed period (1997 to 2000, 2001 to 2004, and 2005 to 2008). Through an analysis of projects that are part of relations of the Executive- Legislative in the city, which are basically ordinary bills, seeks to show qualitatively the areas of concentration of projects and aspects of political negotiation they have. Also noteworthy is the use of two standard indices to analyze the importance of each of the powers in the set of policy decisions in the municipality, which are the data rate and success rate dominance. Finally, among the global analysis of the legislative process, it was discovered that the performance of councilors over a legislature and its behavior on the basis of an opposition or in government, can be inferred from the use they make of two legislative means worthless law, these devices are accounted for in its legislative output: indications and applications. The research concludes that there are differences between these ...